2005
DOI: 10.1016/j.econlet.2004.12.002
|View full text |Cite
|
Sign up to set email alerts
|

ICT diffusion and potential output growth

Abstract: L'augmentation durable des gains de productivité induite par la diffusion des TIC est de nature à élever le rythme de la croissance potentielle, durablement via les effets de substitution capitaltravail et les gains de productivité globale des facteurs (PGF) et plus transitoirement du fait de l'ajustement retardé des salaires sur les gains de productivité. Les ordres de grandeur auxquels aboutissent les éléments d'évaluation présentés montrent que l'effet de moyen-long terme pourrait être important. L'existenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…On this backdrop, numerous studies have discussed the economic impacts of ICT. Cette, Mairesse, and Kocoglu (2005) showed that ICT diffusion contributes to potential output growth in the long-term and to productivity enhancements in the short-term.…”
Section: Ict Diffusion and Economic Growthmentioning
confidence: 99%
“…On this backdrop, numerous studies have discussed the economic impacts of ICT. Cette, Mairesse, and Kocoglu (2005) showed that ICT diffusion contributes to potential output growth in the long-term and to productivity enhancements in the short-term.…”
Section: Ict Diffusion and Economic Growthmentioning
confidence: 99%
“…A model similar in structure to the present one but with a quite different interpretation is in Barro and Sala-i-Martin (1995), chapter 5. The two-sector model with faster technical progress in investment goods was revived by Whelan (2001) and applied by Martin (2001) to study the U.S. economy and by Cette et al (2005) to compare France and the U.S. It was also employed by Bakhshi and Larsen (2005) to analyse the impact of macroeconomic shocks in the U.K. context.…”
Section: Making Projections With the One-sector Growth Modelmentioning
confidence: 99%
“…The moment that positive influence is extinguished it may make conducting adequate monetary policy more difficult (see also: MEIJERS, 2006, pp. 1-23; CETTE, MAIURESSE, KCOGLU, 2004).…”
Section: Monetary Consequences Of Nairu "Flattening"mentioning
confidence: 99%